2021
DOI: 10.3390/curroncol28060387
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Inhibitor Maintenance Therapy Combined Iodine-125 Seed Implantation Successfully Salvage Recurrent Cervical Cancer after CCRT: A Case Report

Abstract: Cervical cancer is the fourth most common cancer in females worldwide. Patients with stage III and IV cervical cancer based on the Federation of Gynecology and Obstetrics (FIGO) classification have higher recurrence rates. Because of organs at risk (OAR) protection and the low indication rate of salvage surgery, the choice of treatment is always challenging. Systemic chemotherapy is palliative and can be performed in conjunction with surgery or radiotherapy; however, it has no significant benefit to survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In recent years, it has been demonstrated that 125I seed implantation can be effectively treat recurrent cervical cancer, leading to improved survival and long-term outcomes for patients [ 7 , 17 ]. Wei and others [ 18 ] also reported a case of immunotherapy combined with 125I seed implantation for the treatment of recurrent cervical cancer following concurrent radiotherapy. This study showed that 125I seed implantation was a safe and effective therapeutic strategy, suggesting its promising potential.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been demonstrated that 125I seed implantation can be effectively treat recurrent cervical cancer, leading to improved survival and long-term outcomes for patients [ 7 , 17 ]. Wei and others [ 18 ] also reported a case of immunotherapy combined with 125I seed implantation for the treatment of recurrent cervical cancer following concurrent radiotherapy. This study showed that 125I seed implantation was a safe and effective therapeutic strategy, suggesting its promising potential.…”
Section: Discussionmentioning
confidence: 99%